Target therapy for high-risk neuroblastoma treatment: integration of regulatory and scientific tools is needed - Ceci, Adriana; Conte, Rosa; Didio, Antonella; Landi, Annalisa; Ruggieri, Lucia; Giannuzzi, Viviana; Bonifazi, Fedele (Frontiers in Medicine, 2023)
Introduction Several new active substances (ASs) targeting neuroblastoma (NBL) are under study. We aim to describe the developmental and regulatory status of a sample of ASs targeting NBL to underline the existing regulatory gaps in product development and to discuss possible improvements. Methods The developmental and regulatory statuses of the identified ASs targeting NBL were investigated by searching for preclinical studies, clinical trials (CTs), marketing authorizations, pediatric investigation plans (PIPs), waivers, orphan designations, and other regulatory procedures. Results A total of 188 ASs were identified. Of these, 55 were considered ‘not under development' without preclinical or clinical studies. Preclinical studies were found for 115 ASs, of which 54 were associated with a medicinal product. A total of 283 CTs (as monotherapy or in combination) were identified for 70 ASs. Of these, 52% were at phases 1, 1/2, and 2 aimed at PK/PD/dosing activity. The remaining ones also included efficacy. Phase 3 studies were limited. Studies were completed for 14 ASs and suspended for 11. The highest rate of ASs involved in CTs was observed in the RAS-MAPK-MEK and VEGF groups. A total of 37 ASs were granted with a PIP, of which 14 involved NBL, 41 ASs with a waiver, and 18 ASs with both PIPs and waivers, with the PIP covering pediatric indications different from the adult ones. In almost all the PIPs, preclinical studies were required, together with early-phase CTs often including efficacy evaluation. Two PIPs were terminated because of negative study results, and eight PIPs are in progress. Variations in the SmPC were made for larotrectinib sulfate/Vitrakvi® and entrectinib/Rozlytrek® with the inclusion of a new indication. For both, the related PIPs are still ongoing. The orphan designation has been largely adopted, while PRIME designation has been less implemented. Discussion Several ASs entered early phase CTs but less than one out of four were included in a regulatory process, and only two were granted a pediatric indication extension. Our results confirm that it is necessary to identify a more efficient, less costly, and time-consuming “pediatric developmental model” integrating predictive preclinical study and innovative clinical study designs. Furthermore, stricter integration between scientific and regulatory efforts should be promoted.